Illocutionary Acts in the Film "Dosen Ghaib: Sudah Malam atau Sudah Tahu" - Sartika, Sartika; Viladelvia, Viladelvia; Haliq, Abdul (The Future of Education Journal, 2025)
This study aims to analyze the form, meaning, and function of illocutionary speech acts in the film "Dosen Ghaib: Sudah Malam atau Sudah Tahu". This study is based on Austin and Searle's speech act theory and uses qualitative descriptive methods. Data collection techniques include listening, recording, transcription, and taking notes, with data triangulation to increase the validity of the results. This study shows that the use of illocutionary speech acts in films not only conveys information, but also builds character, creates tension, and develops the storyline.